2019
DOI: 10.1016/j.jcou.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of microalgae strains for CO2 capture purposes

Abstract: In this paper we have compared eleven microalgae/cyanobacteria strains used for the development of a CO 2 capture process. Firstly, we studied the tolerance of the selected strains to the water quality available at the production site. The results confirmed that no toxins were present in the water used; in addition, we confirmed that fertilizers could be utilised as the nutrient source instead of pure chemicals. Secondly, the strains were evaluated in terms of growth rate, biomass productivity and photosynthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Cheng et al [48] reported that the amount of CO 2 present in the air (0.04%) is inadequate to achieve high cell density and on the other hand, an excess may inhibit the carbonic anhydrase enzyme, which in turn may reduce biomass productivity. Sepulveda et al [49] reported that S. almeriensis was one of the most productive strains when using it in CO 2 capture processes, with a biomass productivity of 1.0 g•L −1 •day −1 and with 2.…”
Section: Effect Of Co 2 Content On Biomass Concentrationmentioning
confidence: 99%
“…Cheng et al [48] reported that the amount of CO 2 present in the air (0.04%) is inadequate to achieve high cell density and on the other hand, an excess may inhibit the carbonic anhydrase enzyme, which in turn may reduce biomass productivity. Sepulveda et al [49] reported that S. almeriensis was one of the most productive strains when using it in CO 2 capture processes, with a biomass productivity of 1.0 g•L −1 •day −1 and with 2.…”
Section: Effect Of Co 2 Content On Biomass Concentrationmentioning
confidence: 99%
“…It is reported that up to 7% of global CO 2 emissions can be attributed to the anthropogenic emission of CO 2 from coal-fired thermoelectric plants (Morais and Costa, 2007). With respect to CO 2 sequestration, different technologies have been investigated, such as using amines or solid adsorbents (da Rosa et al, 2016;Sepulveda et al, 2019). Cardias et al (2018) reported that the growth of Spirulina sp.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the cultivation of Neochloris strains has significantly increased over the last decade due to its potential to treat wastewater treatment (Altunoz et al 2020;Singh et al 2020), to accumulate significant amounts of lipids suitable for biodiesel production (Banerjee et al 2019), and its capacity to capture a substantial amount of CO 2 (Zhu et al 2018;Sepulveda et al 2019). In addition, the capacity of Neochloris to grow in fresh and marine medium has increased the interest in exploring its full potential (Safi et al 2020).…”
Section: Productionmentioning
confidence: 99%